Contemporary practice and technique‐related outcomes for radical prostatectomy in the UK: a report of national outcomes. (22nd October 2014) - Laird, Alexander; Fowler, Sarah; Good, Daniel W.; Stewart, Grant D.; Srinivasan, Vaikuntam; Cahill, Declan; Brewster, Simon F.; McNeill, S. Alan; British Association of Urological Surgeons (BAUS)
<x xml:space="preserve">Abstract</x> Objective To determine current radical prostatectomy (RP) practice in the UK and compare surgical outcomes between techniques. Patients and Methods All RPs performed between 1 January 2011 and 31 December 2011 in the UK with data entered into the British Association of Urological Surgeons (BAUS) database, were identified for analysis. Overall surgical outcomes were assessed and subgroup analyses of these outcomes, based on operative technique [open RP (ORP), laparoscopic RP (LRP) and robot‐assisted laparoscopic RP (RALP)], were made. Continuous variables were compared using the Mann–Whitney U‐test and categorical variables using the Pearson chi‐squared test. Univariate and multivariate binary regression analyses were performed to assess the effect of patient, surgeon and technique‐related variables on surgical outcomes. Results During the study period 2163 RPs were performed by 115 consultants with a median (range) of 11 (1–154) cases/consultant. Most RPs were performed laparoscopically (ORP 25.8%, LRP 54.6%, RALP 19.6%) and those performing minimally invasive techniques are more likely to have a higher annual case volume with <1% ORP, 39% LRP and 62% RALP being performed by consultants with an annual caseload of >50 cases/year. Most patients were classified as having intermediate‐ or high‐risk disease preoperatively (1596 patients, 82.5%) and this increased to 97.2% (1649) on postoperative risk stratification. The overall intraoperative complication rate was 14.2% and was significantly greater for LRP (17.8%) vs ORP (8.2%) and RALP (12.4%), (P < 0.001). In all, 71% of patients had an estimated blood loss (EBL) of <500 mL, although there were significantly more patients undergoing ORP with >500, > 1000 and >2000 mL EBL compared with the other techniques (P < 0.001). The postoperative complication rate was 10.7% overall, with a significantly greater postoperative complication rate in the LRP group (LRP 14.6%, ORP 8.8% and RALP 10.3% respectively, P = 0.007). Positive surgical margin (PSM) rates were 17.5% for pT2 disease and 42.3% for pT3 disease. The PSM rate was significantly lower in the RALP patients compared with the ORP patients for those with pT2 disease (P = 0.025), while there was no difference between ORP and LRP (ORP 21.7%, LRP 18.1% and RALP 13.0%). There was no significant difference in the PSM rate in pT3 disease between surgical techniques. Conclusion Most RPs in the UK are performed using minimally invasive techniques, which offer reduced blood loss and transfusion rates compared with ORP. The operation time, complication rate, PSM rates, and association with higher volume practice support RALP as the minimally invasive technique of choice, which could have implications for regions without access to such services. The disparity in outcomes between this national study and high‐volume single centres, most probably reflects the low median national case volume, and combined with the positive effect of high case volume on multivariate analysis of surgical outcomes and PSM rates, strengthens the argument for centralisation of services.